Flashback posttraumatic stress disorder, suicide, and the lessons of war - Coleman, Penny (Beacon Press, 2006)
In the early 1970s, Penny Coleman married Daniel, a young Vietnam veteran and fellow photographer. Soon, Daniel became deeply troubled, falling victim to multiple addictions and becoming strangely insecure. He suffered from what we now call posttraumatic stress disorder (PTSD). After Coleman left him, he committed suicide.